Interpretación litológica del pozo centenera 1 mediante “cross-plot” sónico- neutrón - Guarochico Moreira, Jorge Andrés (2009)
The aim of this project is to optimize as much as possible the information you have closed a well known former Centenera 1, through the study of loggs that were in it. This will consider various stages of optimization, improving the format of the analog loggs for using this digital values and improve the geological information from around the hole, making a lithological column, which will choose the area of interest hydrocarbon content ; within this area of interest is assigned a lithology interpreted in different packages, and the values of neutron and sonic is a crossplot neutron or sonic crossover chart, which are obtained the distinction of four groups of lithologies, so that contribute to existing information from the well, this is crossplot of the area was defined as interesting.